Analisis dan Perencanaan Struktur Perkerasan Lentur Jalan Berdasarkan MDPJ No. 03/M/BM/2024 - Robiatul Adawiyah; Akhmad Gazali; Tezar Aulia Rachman (Universitas Sarjanawiyata Tamansiswa, 2026)
The revision of pavement design standards may significantly influence the determination of pavement thickness and structural configuration. This study aims to determine the design thickness of flexible pavement structure on the Kampung Baru – Beruntung Jaya road section based on the Manual Desain Perkerasan Jalan (MDPJ) No. 03/M/BM/2024 and to compare the results with MDPJ No. 02/M/BM/2017. The research employed a quantitative approach using traffic data (LHR and axle loads) and subgrade strength (CBR) as primary design parameters. The analysis shows that, based on Design Chart-4 of MDPJ 2024, the required pavement structure consists of 50 mm HRS-WC, 150 mm LFA Class A, and 150 mm LFA Class B (or natural gravel/stabilized layer with CBR > 10%). Compared to MDPJ 2017, MDPJ 2024 applies refined traffic classification and stricter CBR criteria, resulting in a more structured and adaptive design approach. The updated methodology provides improved technical control over pavement thickness determination and has the potential to enhance long-term pavement performance and reliability.